Make the Most of Your Workday : Be More Productive, Engaged, and Satisfied As You Conquer the Chaos at Work. - Camuto, Mary A. (Career Press, 2018)
Even if you don't have your dream job, every day is precious and filled with opportunities. Make the Most of Your Workday challenges you to actively manage and make the most of workday possibilities and problems. With drive, determination, and optimism, it offers solutions to workday predicaments. You can take control; you don't have to wait for leaders, people, or circumstances to change. No matter your level, situation, or dilemma, Mary shows you how to regroup, reframe, and bounce back. Make the Most of Your Workday begins with six common scenarios. Can you relate to any of the following challenges? Getting caught up in office dramas. Watching workloads increase while resources decrease. Feeling your interest, enthusiasm, and focus fade. Yearning for effective leadership. Wanting to avoid working with certain people. Feeling at the mercy of technology. Make the Most of Your Workday contains powerful strategies and tools from several key areas and combines them into a concise practical guide, from strengthening your mindset and self-awareness to identifying needs and goals, from prioritizing your time and energy to communicating effectively and managing the unexpected.